Functional black phosphorus nanosheets for mitochondria-targeting photothermal/photodynamic synergistic cancer therapy. Issue 13 (28th February 2019) - Yang, Xiaoyan; Wang, Dongya; Zhu, Jiawei; Xue, Lei; Ou, Changjin; Wang, Wenjun; Lu, Min; Song, Xuejiao; Dong, Xiaochen
Abstract : A mitochondria-targeting nanosystem, BP@PDA–Ce6&TPP NSs, has been constructed, and exhibit excellent performance in imaging-guided synergistic photothermal and photodynamic cancer therapy. Abstract : Organelle-targeting nanosystems are envisioned as promising tools for phototherapy, which can generate heat or reactive oxygen species (ROS) induced cytotoxicity in the targeted location but leave the surrounding biological tissues undamaged. In this work, an imaging-guided mitochondria-targeting photothermal/photodynamic nanosystem has been developed on the basis of functionalized black phosphorus (BP) nanosheets (NSs). In the nanosystem, BP NSs are coated with polydopamine (PDA) and then covalently linked with both chlorin e6 (Ce6) and triphenyl phosphonium (TPP) through carbodiimide reaction between the amino group and the carboxyl group, forming BP@PDA–Ce6&TPP NSs. Due to the strong absorbance of BP@PDA in the near-infrared region and the highly efficient ROS generation of Ce6, the as-prepared nanosystem with mitochondria-targeting capacity (TPP moiety) shows remarkably enhanced efficiency in cancer cell killing. Combined photothermal and photodynamic therapy is implemented and monitored by in vivo fluorescence imaging, achieving excellent performance in inhibiting tumor growth. This study presents a novel nanotheranostic agent for mitochondria-targeting phototherapy, which may open new horizons for biomedicine.